Indonesians in Saudi Arabia: Worhsip and Work - Laurence Husson (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1997)
This article, which opens a new line of research, is intended to make a first assessment of the consequences of Indonesian migration to saudi Arabia, in particular during the first half of the 2Oth century-a period when the immigration is bound up with the pilgrimage from which Saudi Arabia draws a large part of its revenues. It must be added that while documentary evidence and partial studies on this period exist, it turns out that documentation on the contemporary period is scarce. This article also is concerned with describing the evolution of certain striking aspects of the close relation between the pilgrimage to Mecca and Indonesian migrants looking for work. We need to consider the methods of hiring labor, the networks involved in recruiting it, the organization of travel, as well as the increasing indebtedness of the migrants through intermediaries who, more and more professionally, arrange these attempts to live abroad, prompted in many cases by the same desire for wealth.DOI: 10.15408/sdi.v4i4.767